Turbulence modeling in the riser of a circulating fluidized bed using CFD sottware - Hussain, Ahmad; Nasir Ani, Farid; Darus, Amer Nordin; Ahmad, Zainal; Mustafa, Azeman (Malaysian Society of Analytical Sciences, 2005)
For the last few decades, Circulating Fluidized Bed Combustion (CFBC) technology is being used to burn biomass waste while meeting stringent emission requirements for con trol of SO 2 and NO x emission. However, complex flow patterns are encountered when heat, mass and momentum heat transfer are interlinked which in turn controls the SO 2 and NO x emissions. 2D simulations were done using FLUENT Ver. 6.1, a CFD pack age by Fluent Inc. Sand particle sand air were used as fluidizing materials. The results discuss the turbulent flow behaviour using k-e turbulence model. The simulations show that velocity profiles along the riser height are influenced by the exit geom etry. The riser exits clearly showed the regions of flow separation and reattachment. The increased turbulence was also reported in riser exits and connector, which in turn yields lower SO 2 and NO x emissions.